Can Tomato Powder Reduce Radiation-Induced Effects in a Murine Model of Prostate Cancer?. (29th May 2020) - Rowles III, Joe; Wallig, Matthew; Selting, Kimberly; Fan, Timothy; Miller, Rita; O'Brien Jr., William; Erdman Jr., John
Abstract: Objectives: Tomatoes contain carotenoids and other potent antioxidants that may protect the surrounding tissue from the detrimental effects of external beam radiation therapy, while reducing rates of prostate carcinogenesis. The objective of this study was to determine whether dietary lyophilized tomato paste (TP) alters early inflammatory and oxidative events following a single dose of radiation and leads to a more successful therapeutic outcome. Methods: Male Transgenic Adenocarcinoma of the Mouse Prostate (TRAMP) mice (n = 76) were provided a powdered AIN-93 G diet (Control) or a modified AIN-93 G diet containing 10% TP (w/w) at 4 weeks of age. Mice were monitored by ultrasound for in vivo tumor detection and 3-D volumetric measurement biweekly. Once tumors reached a volume of 1000 mm 3, the caudal half of the mouse was irradiated with 7.5 gy (Rad, n = 18–19 per diet) or 0 gy (sham, n = 16–20 per diet) with a Cobalt-60 source. Mice were euthanized 24 hours after radiation or sham treatment. Antioxidants (carotenoids and α-tocopherol) were measured by high performance liquid chromatography (HPLC) in the serum, tumor, prostate, and liver. Sections of tumor, liver, kidneys, bladder, lymph, bladder and intestines were stained by hematoxylin and eosin (H&E) and cleaved-caspase 3 were assessed for radiation-induced changes and apoptosis. Inflammatory markers (C-reactive protein, IL-6, IL-17A, TNFα, IFNγ, and IL-10) were measured in serum, liver, prostate, tumor, and epididymal adipose tissues by ELISA. Results: This study is the first to explore the effects of TP on the tumor microenvironment following irradiation. Initial results suggest that TP consumption does not alter circulating or tissue (liver and prostate) concentrations of inflammatory markers (C-reactive protein, TNFα, IFNγ, IL-6, IL-17, or IL-10). We hypothesize that TP-Rad will maintain similar levels of circulating concentrations of antioxidants (carotenoids and α-tocopherol) compared to sham-treated mice. Additionally, we hypothesize that TP will reduce markers of cell damage in surrounding tissues. Conclusions: This study will provide important preclinical data to inform future clinical trials evaluating approaches to lessen extra-prostatic damage from radiation therapy and thus improve therapeutic outcomes. Funding Sources: This work was supported by USDA NIFA ILLU-971–334.